Autonomic intelligence evolved cooperative networking - Wódczak, Michal (Wiley series on cooperative communications, 2018)
Autonomic Intelligence Evolved Cooperative Networking offers a comprehensive advancement of the state-of-the art technological developments in the fields of Cooperative Networking and Autonomic Computing. Based on his track record in industrial standardisation, as well as academic and applied research, the author presents a fully-fledged Autonomic Cooperative Networking Architectural Model that encompasses the relevant workings of both the Layers of the Open Systems Interconnection Reference Model and the Levels of the Generic Autonomic Network Architecture